Real interest rate convergence among G7 countries - Jana Riedel (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We analyze real interest rate convergence among six industrialized countries in between 1975M1-2011M3 within a multi-country framework by means of a dynamic latent factor model. The real interest rates are decomposed into permanent and transitory factors, and country-specific components. Time-varying variances allow for an endogenous transition from a high variance regime at the beginning of the sample towards a low variance regime. The estimation results suggest that four permanent and four transitory components capture the real interest rate dynamics among the sample of industrialized countries. The common component variances mostly decline over time, and in part even converge to values close to zero. This indicates a reduction in the number of stochastic components over time, which can be interpreted as confirmation of the convergence hypothesis. We observe rapid convergence during the late 1970s and 1980s, followed by slower transition since the mid-1990s when financial markets had already been highly integrated.
Keywords: C32; F36; F32; 330